REFORMULASI TATA KELOLA KEUANGAN MASJID MENUJU REVOLUSI MASJID 4.0. - Anita Putri; Raya Puspita Sari Hasibuan (Wahana Islamika: Jurnal Studi Keislaman, 2021)
The mosque is one organization that has not been ableto adapt to technological advances. This results in the mosque'sresources being not managed optimally. The purpose of thisstudy was to describe the application of technology to thefinancial management of mosques in Binjai City and, to conducta SWOT analysis of mosque financial governance. This studyuses field data, and analyzes the data using qualitative methods.The results of this study indicate that the implementation oftechnology in mosque financial management is very minimal,this is indicated by the large number of handwritten mosquefinancial reports because the administrators cannot operatecomputers. the administrators, the drawbacks are technologicalstuttering, minimal innovation, minimal training, lack ofgeneration x, y, z, the opportunities they have are technologicaldevelopments, modernist civilization, economic stability, and thethreat is hedon culture and erosion of faith.